Convective MHD Flow of a Rotating Fluid Past through a Moving Isothermal Plate under Diffusion-Thermo and Radiation Absorption - Mridusmita Bormudoi; Nazibuddin Ahmed (Journal of Heat and Mass Transfer Research, 2023)
The current article studies the impact of radiation absorption and diffusion thermo effect or the Dufour effect on a convective MHD flow of a rotating fluid past through a moving vertical isothermal plate under thermal radiation, chemical reaction, and heat source. The equations that govern the flow, are transformed into dimensionless ordinary differential equations(ODEs), which are then solved analytically using the perturbation technique. The pertinent results obtained are illustrated graphically for the various relevant thermophysical parameters involved in the problem. Additionally, we have listed the numerical values showing the changes in the viscous drag, rate of heat transfer and mass transfer rate through tables. In the investigation, we observe that the velocity of the fluid accelerates for increasing Dufour number, radiation absorption, and heat source parameter. On the other hand, the velocity retards due to rotation and chemical reaction parameters. The momentum transfer rate upgrades for the Dufour number and radiation absorption parameter.